Mycotoxin communications: Managing messages for different audiences - Leslie, John F.; Morris, Jeffery B.; Gurung, Jaya K.; Harvey, Jagger J. W.; Ayalew, Amare; Baker, Robert; Zhang, Guangtao (Frontiers in Sustainable Food Systems, 2023)
Mycotoxins, such as aflatoxins, fumonisins, trichothecenes, and zearalenone, are increasing in visibility as a public health threat through both acute and chronic exposure in food. USAID through its Feed the Future program has sponsored research in Nepal on mycotoxin contamination and the correlated high levels of stunting in children under age five. Communicating about mycotoxins is a complicated matter, as is communicating about any potentially serious economic or health threat that may be difficult to control. Two nominal group workshops in Nepal focused on identifying problems from multiple perspectives and developing potential communication strategies to mitigate the problem and potential concerns about it. Target audiences were identified along with their interests and effective channels to communicate with and within them. The first audience to work with is the government, as they must understand and value the problem and to generate confidence in potential regulatory and mitigation processes. Producers, educators and health professionals are the next audiences to address as they are the most closely involved with the problem. Consumer engagement is last, with a communication goal of sharing information while minimizing public concern.